A Surprising Role for the Sch9 Protein Kinase in Chromosome Segregation in Candida albicans - Varshney, Neha (Genetics, 2015)
The AGC kinase Sch9 regulates filamentation in Candida albicans. Here, we show that Sch9 binding is most enriched at the centromeres in C. albicans, but not in Saccharomyces cerevisiae. Deletion of CaSch9 leads to a 150- to 750-fold increase in chromosome loss. Thus, we report a previously unknown role of Sch9 in chromosome segregation.